Effects of Peroxiredoxin 6 and Its Mutants on the Isoproterenol Induced Myocardial Injury in H9C2 Cells and Rats. (26th March 2022) - Mu, Runhong; Ye, Siping; Lin, Rui; Li, Yupeng; Guo, Xiao; An, Liping
Abstract : Background. Peroxiredoxin 6 (PRDX6) is an important antioxidant enzyme, with a potential application value in the treatment of diseases caused by oxidative damage. Methods. PRDX6 and a mutant (mPRDX6) were heterologously expressed by using an E.coli expression system and purified by Ni-affinity chromatography. Isoproterenol (ISO) was used to induce a myocardial cell injury model and an animal myocardial injury model. After the treatment with PRDX6 and mPRDX6, the proliferation activity of H9C2 cells was detected by Cell Counting Kit-8 (CCK8) method; the apoptosis was evaluated by flow cytometry, and the histological changes of myocardial cells were observed by hematoxylin and eosin (H&E) staining, the levels of catalase (CAT), glutathione peroxidase (GPX), malondialdehyde (MDA), and superoxide dismutase (SOD) in ISO-treated H9C2 cells as well as in the heart tissue and serum of rats treated with ISO were detected, and the expression levels of Bax, Bcl-2 and peroxisome proliferators-activated receptors- γ (PPAR- γ ) proteins were detected by Western blot. Results. PRDX6 and mPRDX6 were successfully expressed and purified. The results of efficacy study showed that the mutant mPRDX6, in which the phospholipaseA2 (PLA2) activity of PRDX6 was deleted by site directed mutation, had a better protective effect against the myocardial injury than PRDX6. CCK8 results showed that compared with that in ISO group, the proliferation activity of H9C2 cells was significantly enhanced (P < 0.01 ), the apoptosis rate was significantly decreased (P < 0.01 ), and the fluorescence intensity of reactive oxygen species (ROS) was significantly decreased (P < 0.01 ) in mPRDX6 group. The results of H&E staining showed that the myocardial injury was alleviated to a certain extent in mPRDX6 group. Compared with those in ISO group, the activities of CAT, GPX, and SOD in H9C2 cells and the heart tissue and serum of rats were significantly increased (P < 0.05 ), while the contents of MDA were significantly decreased (P < 0.05 ). Western blot analysis showed that the expression level of Bcl-2 in H9C2 cells was significantly decreased (P < 0.01 ), and that of Bax and PPAR- γ was significantly increased (P < 0.05 ). Conclusion. mPRDX6 has a protective effect against the myocardial injury induced by ISO, and the mechanism may be related to its antioxidation. This study may provide a theoretical basis for the research and development of drugs used for the treatment of myocardial injury.